IET 11th International Conference on Ionospheric Radio Systems and Techniques (IRST 2009) 2009
DOI: 10.1049/cp.2009.0033
|View full text |Cite
|
Sign up to set email alerts
|

Capacity estimation of HF-MIMO systems

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Moreover, the small dispersion in elevation and azimuth angles for incident waves at the receive site requires an additional spacing increase to reduce the channel correlation. Finally, the implementation of a standard MIMO solution at HF appears unrealistic for a reason of available space [2,3] and prohibitive wire lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the small dispersion in elevation and azimuth angles for incident waves at the receive site requires an additional spacing increase to reduce the channel correlation. Finally, the implementation of a standard MIMO solution at HF appears unrealistic for a reason of available space [2,3] and prohibitive wire lengths.…”
Section: Introductionmentioning
confidence: 99%
“…They maintained a BER of around 10 −3 , which is considered acceptable for an HF modem. In [ Abbasi et al , ] and [ Gunashekar et al , ] the authors increased the channel capacity using MIMO due to the low cross correlation of signals transmitted and received by different antennas. They concluded that to achieve a lower cross‐correlation factor, the homogeneous arrays should be replaced by collocated antennas and heterogeneous arrays.…”
Section: Polarization Diversity In Hf Literaturementioning
confidence: 99%
“…Due to its low frequency and for frequency division multiplexing purposes, the HF radio channels have a limited useable bandwidth, i.e., 3-20 kHz [3], which in turn limits the rate of information that can be delivered over the channels. Multiple-input multiple-output (MIMO) antenna structure has been considered to improve channel capacity, not only in terrestrial wireless channels [4,5] but also in HF skywave channels [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, researchers have recognized the importance of the characteristic waves, the extraordinary (X) and ordinary (O), that in general are elliptically polarized with opposite senses, in realizing polarization diversity and HF skywave MIMO communications without the need of large spacing between antennas [7][8][9][10][11][12][13][14]. While [7][8][9][10] discover, by simulation and experiment, a lower correlation among subchannels and a greater capacity gain over SISO channels when an antenna structure with two complementary circular polarizations is used compared to a system with linearly polarized antennas, [14] shows mathematically that linearly-polarized antennas can achieve polarization diversity.…”
Section: Introductionmentioning
confidence: 99%